Apakah discovery learning dapat menumbuhkan keterampilan berpikir kritis? Respon siswa terhadap penggunaan UKBM pada Program Ilmu Sosial - Sukartiningsih, Sri; Sarmini, Sarmini; Jacky, Muhammad; El Rizaq, Agung Dwi Bahtiar (Universitas Negeri Malang, 2021)
Critical thinking is one of the main skills that students must mastered in order to respond the challenges of globalization and the demands of skilled labor in this disruption era. Various learning models, methods and strategies are developed to meet these objectives. One of the way is the implementation of teaching materials in the form of Independent Learning Activity Unit (UKBM) in learning to foster students' critical thinking skills. The focus of this study is to describe students' responses to the implementation of UKBM in social science programs based on discovery learning to foster students' critical thinking skills. This study used an explanatory mix method research design with a percentage technique. Data were collected through questionnaires, observations and interviews. Data analysis was carried out in four stages; collection, reduction, presentation and drawing conclusions. This study found several things: 1) UKBM in social science programs are effectively foster critical thinking skills; 2) the most prominent assessment is the aspect of student interest in an attractive UKBM design; 3) the assessment is less prominent in the aspect of discovery learning approach in learning because it requires a long time and seriousness of teachers and students. This paper recommends the implementation of other learning models at UKBM to foster critical thinking skills. DOI: http://dx.doi.org/10.17977/um022v6i12921p9